O papel do agente literário no mercado editorial - Pedersoli, Ana Clara Leite [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (ABECIN, 2020)
O capítulo de livro é um recorte de um estudo mais abrangente acerca do mercado editorial brasileiro e suas estratégias de comercialização, realizado em âmbito acadêmica em nível de iniciação científica. Aborda o agente literário e seu papel diante do mercado editorial de livros.

The book chapter is an excerpt from a more comprehensive study about the Brazilian publishing market and its marketing strategies, conducted within an academic context at the undergraduate scientific initiation level. It addresses the literary agent and their role in the book publishing market.
Keywords: Mercado editorial; Editorial market